Penerapan Akuntansi Manajemen Berbasis Aktivitas Pada Perusahaan Manufaktur - Oktarina Harahap; Maya Macia Sari; Saria Yiska Panggabean; Luthvia Aulia; Atika Atika (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research was conducted to analyze the application of Activity Based Management to improve cost efficiency in manufacturing companies. The method used in this research is qualitative method. Based on the analysis that has been done by applying Activity Based Management has a positive impact on the company in order to obtain the expected cost efficiency so as to increase the profits generated by the company. To achieve this goal, the company must carry out several stages, besides that by applying Activity Based Management the company can save costs incurred by the company. Activity Based Management emphasizes activity management, or activity analysis, in its application.